CONCEPT OF MODERN CONTROL SYSTEMS ON TWO STROKE REVERSE UNIFLOW COMBUSTION ENGINE (Perner's Contacts, 2014)
Next level of passenger vehicles engines evolution is needed to comply with fuel economy and pollutant regulation legislative requirements. Turning a combustion engine with modern control systems into reverse uniflow two-stroke engines improves the power density of the engine and minimizes negative aspects of using the classic two-stroke engines. Variable valve timing allows control of the intake stroke, forced induction by supercharger substitutes intake into two-stroke engine crankcase, high pressure direct fuel injection eliminates fuel losses caused by overlapping intake and exhaust strokes. Future research will focus on the new design proof of concept and particular technical solutions.
Keywords: uniflow two-stroke engine; valvetrain; forced induction; direct fuel injection